Modernization of Nursing Education and Nurse' It Competence - Šakalytė, Danguolė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The use of technology in nursing is not new; in fact, nurses have become proficient in utilizing and adapting complex technology into caring nursing practice. Since nurses are the largest group of health care providers, discipline-specific competencies in the use of ICT and other technologies are imperative. This realization has catalyzed the steady development of nursing informatics. Nursing schools demonstrate use of recognized approaches to teaching and learning in their programs, including, but not limited to, adult education, self-directed learning, e-learning and clinical simulation. The article’ aims are to review modernization of nursing education and to assess nurse’ IT competence according to professional skills comparing groups with different educational background and work experience.